Olhar para além das enfermidades: ser liberto na provincia do Ceará - Caxile, Carlos Rafael Vieira (2005)
Initially this work looked for through the analysis of Sent Correspondences, Occupations, Proceedingses, Annals of the Camera and Newspapers of Time to evidence the process of extinction of the servile element in the county of Ceará unchained by the societies libertadoras, specifically the society Perseverance and Future and Society From Ceará Libertadora. The partner-political and economic context was demonstrated in that they appear, as well as the factors that facilitated the county of Ceará to be the first to free its slaves four years before the Empire, on March 25, 1884. Soon after analyzing, mainly, Actions of Freedom, the important paper was evidenced that had the law 2040 of September 28, 1871 for the juridical direction of slaves' freedom in Brazil. It was sought starting from the parliamentary embates to notice the social experiences of the system escravista vivenciados for gentlemen and slaves and to relate them to the projects of direction of a free society. It is finally it analyzed and he/she/it discussed some literary works written in Brazil, mainly, in Ceará, starting from the second half of the century XIX that were about the condition of the African and afro-descending. Focalizou-if specifically poetries and romances of romantic-naturalistic character.